UJI KESESUAIAN PESAWAT PANORAMIC CHEPALOMETRIC DI LABORATORIUM JURUSAN TEKNIK RADIODIAGNOSTIK DAN RADIOTERAPI, POLTEKKES KEMENKES SEMARANG (UJI MENGGUNAKAN FILM GAFCHROMIC) - Andrey Nino Kurniawan; Dwi Rochmayanti; Agustina Dwi Prastanti (JRI (Jurnal Radiografer Indonesia), 2023)
ABSTRACT Background: X-ray equipment used for radiographic examination according to Bapeten regulations must undergo a compliance test, both for new installation and for relocating. The Panoramic Chepalometry in the Department of Radiodiagnostics and Radiotherapy Techniques Semarang is a new device and has undergone a relocation from the initial installation. In addition, the unique condition of the Panoramic Chepalometry is direct image processing or direct radiography, so a special method is needed for testing x-ray collimation beams, namely using gafchromic films Methods: The research is experimental with a one shot case study at the Laboratory of the Department of Radiodiagnostic and Radiotherapy Techniques, Poltekkes Kemenkes Semarang. The research object is a Panoramic cephalometry device. The measuring instrument used was Raysave, and the test parameters measured were: X-ray beam, voltage accuracy, time accuracy, linearity, reproducibility, HVL, and tube container leakage. The analysis of the test results is adjusted to Bapeten regulation no. 2 of 2018 Results: Parameter test results obtained: X-ray beam is still within normal limits, voltage accuracy measurement results obtained a maximum error of 2.73% (max. limit 6%), time accuracy obtained a maximum error of 7.8% (max. limit 10 %), linearity was not measured because the mA value was fixed, reproducibility was obtained CV at a voltage of 0.0012 and radiation output of 0.0006 (CV≤ 0.05), x-ray beam quality (HVL) was obtained at 3.72 mm Al at 80 kVp (HVL limit ≥ 2.3 mm Al), and no leakage in the tube housing Conclusions: The results of the panoramic cephalometric compliance test at the Laboratory of the Department of Radiodiagnostic and Radiotherapy Techniques, Poltekkes Kemenkes Semarang, on 7 test parameters as a whole are still within normal limits according to Perka Bapeten no.2 of 2018